Reconhecimento de gestos aplicado as áreas da saúde : mudança de paradigma na interação humano computador por meio de estímulos motores e cognitivos - Brandão, Alexandre Fonseca (Universidade Federal de São Carlos, 2015)
Taking into consideration the culture and the lifestyle as prevention and health promotion strategies the idea was to provide users with non-conventional means of interacting with the Virtual Reality (VR) environment, using motor gestures in a physically active an essentially playful way. The set of applications was developed to be controlled using a gesture recognition sensor (Kinect – Microsoft), which scans the user’s body using an infrared camera. A set of applications called GestureCollection, represented by GestureChair – it was developed from a free version of the Pacman game and gives to the user the possibility of controlling the game using his hands (up, down, left or right). It was initially directed to spinal cord injury, which causes paraplegia and compromises the function of lower limbs but not the upper limbs, but in principle, it can be applied to any condition that partially disables upper limbs. GesturePuzzle – it was implemented as a virtual puzzle game where the user mounts an image from separate parts. The interaction with the VR environment occurs through natural movement of picking up and dropping the pieces where the user freely explores the shoulder joint in all planes of motion. GestureChess – it was developed to control a chess game, in which the first movement is a click that creates the origin of a spatial coordinate system. From this point it is possible to associate hand movements to pointer coordinates thus controlling the game. This is an application indicated to users who require intense cognitive stimulation related, in this case, to the calculation of probabilities required by chess game itself. Simultaneously, it is useful for upper limb stimulation. GestureMaps – it was developed for the exploration of geographic maps in Google Streetview. This application is controlled by body gestures, namely lower limb lifting (to simulate walking) and trunk rotation to the right or left (according to the desired direction). It was proposed having in mind elderly people who have spatial disorientation. Finally, RehabGesture - This software allows the measurement of range of motion (in the coronal plane) 0° extension to 145º of flexion of the elbow joint and from 0° aduction to 180° of abduction of the glenohumeral (shoulder) joint, leaving the standing position. The presented applications (GestureCollection) allow muscle recruitment at different speeds and ranges of motion, training of general motor coordination, and cognitive stimulation in situations of dual task performed in virtual environments, with gestural control.
Gesture recognition applied to health areas
Keywords: Reconhecimento de gestos; Interação humano-computador; Estímulo motor; Estímulo cognitivo; Realidade virtual; Atividade física; Gesture recognition; Human computer interaction; Motor stimuli; Cognitive stimuli; Virtual reality; Physical activity; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO